Experimental determination of bone cortex holding power of orthopedic screw - Bolliger Neto, Raul; Rossi, João D. M. B. Alvarenga; Leivas, Tomaz Puga (Revista do Hospital das Clínicas, 1999)
Cylindrical specimens of bone measuring 15 mm in diameter were obtained from the lateral cortical layer of 10 pairs of femurs and tibias. A central hole 3.2 mm in diameter was drilled in each specimen. The hole was tapped, and a 4.5 mm cortical bone screw was inserted from the outer surface. The montage was submitted to push-out testing up to a complete strip of the bone threads. The cortical thickness and rupture load were measured, and the shear stress was calculated. The results were grouped according to the bone segment from which the specimen was obtained. The results showed that bone cortex screw holding power is dependent on the bone site. Additionally, the diaphyseal cortical bone tissue is both quantitatively and qualitatively more resistant to screw extraction than the metaphyseal tissue.